A review of the motivation theories in learning - Gopalan, Valarmathie; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir; Alwi, Asmidah; Che Mat, Ruzinoor (2017)
Motivation and learning process have a deep connection.Motivation is the core for human being’s aspirations and achievements.Thus, motivation is crucial to succeed in educational matters and without the fighting spirit nothing is possible not only in education but also in real life.The learning process is an endless life long process.In order to continuously achieve a high motivation is crucial. Motivation is the force that encourages students to face all the tough and challenged circumstances. Motivation itself is a huge scope to cater.Hence, this study emphasizes on several motivational theories that are related to the learning domain.